Análisis del comportamiento del consumidor de los servicios del patio de comidas del Paseo Shopping de la ciudad de Machala - Mayón Cango, Jhonny Paúl (2015)
Market options abound to cover the same need, and the consumer is faced with a variety of products and vendors that can provide, however, understand the process by which consumers make decisions, choose the goods and satisfy your needs is not easy. A seller usually uses a set of tactics to persuade a consumer and this will probably buy the weariness that causes the seller, although looking more to gain effective customer has lost a potential consumer, therefore, all those responsible the sale must be able to understand and predict consumer behavior in order to design and employ appropriate strategies to interact tactics, achieving a favorable negotiation for both sides, that is a win-win customer / vendor. This research seeks to analyze the profile of the consumer food court Paseo Shopping Mall and for this it has been decided to divide the work into three chapters, focus and concepts, integrative proposal and finally the implementation phases. The first deals with the methodology and theoretical framework, the report findings and conclusions. Finally, the annexes and the model with the tabulated survey results can be seen the results tabulated with their respective tables and graphs are additional. Finally it is expected that the integrative approach allows a bidirectional communication between the consumer and the client, and in this way to achieve higher sales and position the place in a place of leadership and positioning, a complex task that is not seen, because there is a great influx and above all a great consumer loyalty over other shopping centers that are located in the city of Machala.